Potential Relevance of Melatonin Against Some Infectious Agents: A Review and Assessment of Recent Research - Kotb Elmahallawy, Ehab; Ortega Luque, Javier; Saleh Aloweidi, Abdelkarim; Gutierrez -Fernandez, Jose; Sampedro-Martinez, Antonio; Rodriguez-Granger, Javier; Kaki, Abdullah; Agil, Ahmad (Current Medicinal Chemistry, 2015)
Melatonin, a tryptophan-derived neurohormone found in animals, plants, and microbes, participates in various biological and physiological functions. Among other properties, numerous in vitro or in vivo studies have reported its therapeutic potential against many parasites, bacteria and viruses. In this concern, melatonin was found to be effective against many parasites such as Plasmodium, Toxoplasma gondii, and Trypansoma cruzi, via various mechanisms such as modulation of calcium level and/or host immune system. Likewise, a recent investigation has reported in vitro activity of melatonin against Leishmania infantum promastigotes which is the causative agent of fascinating visceral Leishmaniasis. This review was initially undertaken to summarize some facts about certain physiological and therapeutic effects of melatonin. It also reviews the effects and action mechanisms of melatonin in bacterial and viral infection besides biology of different parasites which may provide a promising strategy for control of many diseases of public health importance.
Keywords: Bacterial and viral infection